Development of a three-dimensional tomography holder for in situ tensile deformation for soft materials. (11th June 2018) - Higuchi, Takeshi; Gondo, Takashi; Miyazaki, Hiroya; Kumagai, Akemi; Akutagawa, Keizo; Jinnai, Hiroshi
Abstract : We developed a novel in situ straining holder for polymeric materials capable of tensile deformation and high-angle tilt for electron tomography. The holder allows large tensile deformation (≃800 µm) with a large field of view, and a high tilt angle (±75˚) during in situ observations. Abstract: An in situ straining holder capable of tensile deformation and high-angle tilt for electron tomography was developed for polymeric materials. The holder has a dedicated sample cartridge, on which a variety of polymeric materials, such as microtomed thin sections of bulk specimens and solvent-cast thin films, can be mounted. Fine, stable control of the deformation process with nanoscale magnification was achieved. The holder allows large tensile deformation (≃ 800 μm) with a large field of view (800 × 200 μm before the deformation), and a high tilt angle (±75°) during in situ observations. With the large tensile deformation, the strain on the specimen can be as large as 26, at least one order of magnitude larger than the holder's predecessor. We expect that meso- and microscopic insights into the dynamic mechanical deformation and fracture processes of polymeric materials can be obtained by combining the holder with a transmission electron microscope equipped with an energy filter. The filter allows zero-loss imaging to improve the resolution and image contrast for thick specimens. We used this technique to study the deformation process in a silica nanoparticle-filled isoprene rubber.